Comprehensive genome annotation of Bombyx mori p50ma strain, a newly developed standard strain - Jung Lee; Toshiaki Fujimoto; Ken Sahara; Atsushi Toyoda; Toru Shimada (Scientific Data)
Abstract B. mori is a model species of lepidopteran insects. The genome assembly has been successively updated since the whole genome sequences were first determined in 2004. In addition, chromosome-scale genome assemblies of not only standard strains but also practical strains have been reported. We successfully constructed a chromosome-scale female genome assembly of p50ma, a standard strain developed by Kyushu University. This assembly is now certified as a ‘reference’ in the NCBI datasets. To improve the usability of this strain, here we report the achievement of gene model construction based on the transcriptome information, followed by functional annotation. The assembly harbours 16,295 protein-coding genes. In addition, to improve gene knockout efficiency, we performed ATAC-seq in early embryos and comprehensively identified open chromatin regions. Finally, small RNA-seq (sRNA-seq) targeting PIWI-interacting RNA (piRNA) was performed in testes, ovaries, and early embryos to identify piRNA clusters comprehensively. These data will increase the usability of p50ma as a standard strain and facilitate NBRP users to exploit this strain.